Pseudotumor cerebri (with special reference to visual loss) - Bryer, Alan (Division of Urology, 2017)
AIMS OF STUDY: 1. To analyse the patients . who have been treated at Groote Schuur Hospital over the last seven years for Pseudotumor Cerebri. 2. To document the clinical features of this group of patients. 3. To determine the visual prognosis of this group. 4. To assess the forms of treatment that have been used in this group. 5. To review the literature with regard to: a) a comparison of the results of other studies with the present one. b) the pathophysiology of the condition. c) treatment of the syndrome. d) the visual prognosis of the syndrome.